A systematic review of local excision combined with chemoradiotherapy for early rectal cancer. (July 2014) - Ung, L.; Chua, T. C.; Engel, A. F.
Abstract Aim Local excision of early rectal cancer is a less morbid alternative to major abdominal surgery. This review evaluates the role of local excision with neoadjuvant or adjuvant chemoradiotherapy to identify a select group of patients where local excision is appropriate without significantly compromising the oncological outcome. Method MEDLINE, PubMed and the Cochrane Central Register of Controlled Trials databases were searched to identify relevant articles investigating the role of local excision with adjuvant or neoadjuvant chemoradiotherapy in patients with T1/T2N0M0 disease. Eleven studies comprising 455 patients were selected. Oncological end‐points included overall survival, disease‐free and disease‐specific survival, recurrence rates as well as perioperative morbidity and mortality. Results At a range of 30.5–115.2 months, median overall survival, disease‐specific and disease‐free survival were 75% (66–80.6%), 89% (75–93.3%) and 74% (64–85.2%), respectively. Median local, distant and overall recurrence rates were 10% (4.8–25%), 4.7% (4–11.8%) and 13.1% (10.7–23.5%), respectively. Mortality was 0% in all studies except one (2.9%). Most reported complications were minor and were treated conservatively. Conclusion This systematic review provides data suggesting that selected patients with T1/T2N0M0 rectal cancer may undergo local excision without compromising the oncological outcome otherwise conferred by total mesorectal excision. It may be a particularly useful option in patients in whom radical surgery is contraindicated. Randomized trials comparing both management strategies to consolidate this finding may lead to a paradigm change in the management of early rectal cancer.